Hybrid abutment during prosthetic planning and oral rehabilitation - Matatos, Jefferson D. [UNESP]; Arcila, Laura V. [UNESP]; Ortirtiz, Laura P. [UNESP]; Lopes, Guilherme R. [UNESP]; Anami, Lilian C. [UNESP]; Ramos, Nathália C. [UNESP]; Saavedra, Guilherme S. [UNESP]; Tribst, João P. [UNESP]; Bottino, Marco A. [UNESP] (Edizioni Minerva Medica, 2022)
INTRODUCTION: The present study aims to describe through a literature review, the characteristics and properties of hybrid abutments, as well as their proper use as a new rehabilitation strategy. EVIDENCEAC QUISITION: A bibliographic search was conducted in the main health databases Pubmed (www.pubmed.gov) and Google Scholar (www.scholar.google.com.br), in which studies published from 2001 to 2020 were collected. Laboratory studies, case reports, systematic and literature reviews were included. Therefore, articles that do not address the characteristics and properties of hybrid abutments were excluded. In addition, studies that did not report the use of hybrid abutments as a new rehabilitation strategy. EVIDENCE SYNTHESIS: According to the inclusion and exclusion criteria, 80 research articles were selected and 20 were excluded, while 25 in vitro, 17 in vivo and 9 in silico studies were reviewed. CONCLUSIONS: The literature demonstrates that hybrid abutments are an excellent alternative in cases of implant-supported rehabilitation, presenting high esthetic results, associated with good soft tissue response, peri implant marginal bone stability and adequate stress distribution during the masticatory loads dissipation.
Keywords: Dental abutments; Dental implants; Rehabilitation